Exercise intensity in tennis: simulated match play versus training drills - Fernandez, J. F.; Fernandez-Garcia, B.; Mendez-Villanueva, A.; Terrados, N. (Medicine and Science in Tennis, 2005)
The purpose of this study was to compare selected physiological responses during simulated singles match play with typical training drills used by male players during on-court practice sessions. There were two parts to the study, with one week separating each part. In Part One, six internationally (ATP) and nationally ranked players completed an incremental treadmill test to exhaustion, which measured maximum oxygen uptake (VO2max) (58,2 ± 2,2 mL. kg-1.min-1), maximum heart rate (HRmax) (191 ± 4 beats.min-1), and lactate concentrations (LA) (6,6 ± 0,7 mmol.L-1). In Part Two, players were asked to complete two tasks on outdoor clay courts. Task One consisted of two different technical (`control`) drills and the second task was a competitive set. Subjects were equipped with a portable metabolic system, which measured oxygen consumption (VO2) and heart rate (HR). During the training drills, oxygen consumption (i.e. VO2 and %VO2max) and average heart rates (i.e. HRmed and %HRmax) were significantly higher (P < 0.01) than during a simulated competitive set. Results from this study suggest that monitoring the physiological workload associated with on-court training drills would assist in optimising training efficacy (i.e. the combined improvement of conditional and technical abilities) in competitive tennis players.